Deficiency of Lipid Phosphatase SHIP Enables Long Term Reconstitution of Hematopoietic Inductive Bone Marrow Microenvironment - Liang, Olin D. (2013)
Dysfunctional bone marrow (BM) microenvironment is thought to contribute to the development of hematologic diseases. However, functional replacement of pathologic BM microenvironment through BM transplantation has not been possible. Furthermore, the study of hematopoietic inductive BM microenvironment is hampered by the lack of a functional non-hematopoietic reconstitution system. Here we show that deficiency of SH2-containing inositol-5′-phosphatase-1 (SHIP) in non-hematopoietic host microenvironment enables its functional reconstitution by wild-type donor cells. This microenvironment reconstitution normalizes hematopoiesis in peripheral blood and BM, also alleviates pathology of spleen and lung in the SHIP deficient recipients. SHIP deficient BM contains a significantly smaller population of multipotent stromal cells with distinct properties which may contribute to the reconstitution by wild-type cells. We further demonstrated that it is the non-hematopoietic donor cells that are responsible for the reconstitution. Thus, we have established a non-hematopoietic BM microenvironment reconstitution system to functionally study specific cell types in hematopoietic niches.